Affective bond with the attachment figures, quality in romantics relationships and self-concept in teenagers of a private university of Lima-Perú - Arias Orezano, Gloria (2019)
Objetive: The objective of the study was to determine the influence of attachment figures (mother, father andpeers) and the quality of romantic relationships about selfconcept in students of both sexes between agesof 16 to 20 years old belonging to a private university in Lima. Methods: The design was not experimental,explanatory scope and cross-section. To that, three instruments were used: Attachment Inventory withParents and Peers (AIPP), the Multidimensional Self Concept Scale Form 5 (SF5) and Quality Inventary inRomantic Relationships (NRI). Results: The results showed that attachment figures and the quality ofromantic relationships can to explain the 44.7% of the variability in self-concept of adolescents. Also it wasidentified that the attachment figures can explain the 43.7% of the self-concept. Similarly, the family selfconcept explain in a 50.4% by attachment figures, being the mother the most influential figure. Continuedto the result, it was identified a 25.9% of variability of social self-concept is explained by attachment withthe peers. On the other hand, the attachment with peers explains a 22.2% the variability of the qualityin romantic relationships. Conclusions: Finally, the quality level in romantic relationships can explain 14% ofvariability in self-concept of teenagers.